Borders in clinical teacher professional development: A concept analysis. Issue 4 (3rd July 2020) - Ryan, Colleen; McAllister, Margaret
Abstract : Background: A career in nursing academia offers clinicians a new challenge. Academic nursing and clinical nursing are two separate worlds with different social and cultural borders, foci and ways of working. It is possible to imagine this space as a kind of borderland, a new frontier that is simultaneously exciting and perilous. Aim: A concept analysis explored the borders as a site of meaning for professional development. Method : This study employed a four step concept analysis. Results: The analysis revealed four attributes of borders that are useful for clinical teachers to understand; liminality, border crossing, border work, and inhabiting a new world. Conclusion: As a liminal space, clinical teaching can be a site where uncertainty and ambiguity arises. This can create anxiety but also opportunities to think about both worlds differently, so that clinical teachers may discover new insights and applications for their work.